Genetic Markers of Spina Bifida in an Indian Cohort - Prabudh Goel; Mahima Sharma; Himani Kaushik; Sourabh Kumar; Harpreet Singh; Vishesh Jain; Anjan Kumar Dhua; Devendra Kumar Yadav; Neeta Kumar; Sandeep Agarwala (Journal of Indian Association of Pediatric Surgeons, 2024)
OBJECTIVE: To identify the genetic markers of spina bifida through a systematic survey of the exome in an Indian cohort. MATERIALS AND METHODS: Three consecutive patients (P1: 1 year, male; P2: 2.8 years, male; and P3: 10 years, female) with spina bifida (lumbosacral meningomyelocele) underwent whole-exome sequencing (libraries: SureSelect Human All Exon V8; sequencing: 2 * 150 bp paired-end run, 100×) with NovaSeq 6000. Data analysis was performed using SMART-One™ (secondary analysis) and SMARTer™ (tertiary analysis) for automated quality check, alignment (GRCh38/hg38), variant calling, annotation (ClinVar, OMIM, avsnp150, 1000 Genomes v5b, ExAC v0.3, gnomAD v4.0, and esp6500vi2all v0.0.25), v0.0.25), interpretation. The pathogenic and likely pathogenic (ClinVar/ InterVar), non-synonymous, exonic markers (read depth ≥ 5) were matched with the Familial Neural Tube Defects (Version 1.10) panel (FNTD panel). Results: Pathogenic variants overlapping with the FNTD panel were MTRR, CC2D2A, and ZIC2 in P1 and P2, TGIF1 in P1 only, and none in P3. Novel pathogenic/likely pathogenic variants common to all three patients were PRUNE1, PKD1, PDZD2, and DAB2 in the homozygous state as well as in the heterozygous state, PLK1 and NLGN2. The possible role of such markers in etiopathogenesis was explored through a literatur search. Conclusions: The genetic landscape of the spina bifida in an Indian cohort is diverse compared to that reported from other parts of the world. A comprehensive catalog of single-nucleotide variants in the etiopathogenesis of the spina bifida on a background of the Familial Neural Tube Defects Panel has been generated.